2008
DOI: 10.1111/j.1365-2044.2008.05485.x
|View full text |Cite
|
Sign up to set email alerts
|

Medication‐related patient safety incidents in critical care: a review of reports to the UK National Patient Safety Agency*

Abstract: SummaryWe reviewed all patient safety incidents reported to the UK National Patient Safety Agency between 1st August 2006 and 28th February 2007 from intensive care or high dependency units. Incidents involving medications were then categorised. 12 084 incidents were submitted from 151 organisations (median 40, range 1-634 ⁄ organisation). 2428 incidents were associated with medication use involving 355 different drugs, most commonly morphine (207 incidents), gentamicin (190 incidents) and noradrenaline (133 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 25 publications
2
42
0
1
Order By: Relevance
“…Many of the problems associated with the prescription and administration of fluid were similar to those previously described for medications [11]. Major complications of vascular access (pneumothorax, cardiac damage or damage to vessels) were only described in 24 incidents.…”
Section: Fluids and Vascular Accessmentioning
confidence: 70%
See 2 more Smart Citations
“…Many of the problems associated with the prescription and administration of fluid were similar to those previously described for medications [11]. Major complications of vascular access (pneumothorax, cardiac damage or damage to vessels) were only described in 24 incidents.…”
Section: Fluids and Vascular Accessmentioning
confidence: 70%
“…Other incident groups were subject to more detailed sub-classification by exporting the incidents to EXCEL spreadsheets and developing sub-classification systems for individual incident groups; these spreadsheets were then also exported to SPSS for subsequent analysis. Medication, medical devices and airway incident groups were not subjected to this sub-classification as we have previously described detailed classification systems for these incidents [9,11,12].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the potential for harm is an accepted definition for a prescribing error. Previous studies have shown harm from simple prescribing errors: 8,9 for example, the use of trade names is associated with greater prevalence of duplication of medications, presumably due to prescribers' failure to recognise identical medications. 3 Another obvious source of harm from simple errors is the inadequate documentation of allergy when omissions could result in the administration of a contraindicated drug.…”
Section: Limitationsmentioning
confidence: 99%
“…A dverse events related to intravenous administration of vasoactive medication are relatively common as the result of preparation and prescription errors 1 ; however, many errors with vasoactive medications have been related to infusion technology, 2 for example, pump malfunctions. 3 In addition, characteristics of the infusion system may yield dosing deviations after interventions, such as a syringe exchange, 4 flow rate changes, 5,6 and vertical displacement of the pump.…”
mentioning
confidence: 99%